A landmark-based 3D parametric foot model for footwear customisation. (2018) - Song, Yu; Hoeksema, Jesse; Ramkumar, Anjana; Molenbroek, Johan F.M.
This paper presents a landmark-based parametric 3D foot model which can be used as the basis for designing customised shoe lasts. 22 points on the surface of the foot are defined as anthropometric landmarks.11 NURBS curves are then generated based on these 22 landmarks to construct the 3D parametric foot surface model using Rhinoceros® and Grasshopper®. Nineteen test subjects participated in an experiment to verify the effectiveness of the proposed model. The mean absolute difference of the ball girth between the 19 models and their corresponding 3D scans was found as 3.53 mm. The mean directed Hausdorff distance between the foot outlines of the models and the 3D scans was identified as 1.40 mm. Regarding the 3D surface, the overall mean bidirectional mean directed Hausdorff distance between the models and the 3D scans of all 19 cases was calculated as 3.68 ± 0.31 mm. Compared to the findings of other researchers, it is concluded that the proposed parametric model can describe the 3D shape of the foot with a reasonable accuracy and it can be used as a basis for shoe last design.